Ecological impacts of atmospheric pollution and interactions with climate change in terrestrial ecosystems of the Mediterranean Basin: Current research and future directions. (August 2017) - Ochoa-Hueso, Raúl; Munzi, Silvana; Alonso, Rocío; Arróniz-Crespo, María; Avila, Anna; Bermejo, Victoria; Bobbink, Roland; Branquinho, Cristina; Concostrina-Zubiri, Laura; Cruz, Cristina; Cruz de Carvalho, Ricardo; De Marco, Alessandra; et al.
Abstract: Mediterranean Basin ecosystems, their unique biodiversity, and the key services they provide are currently at risk due to air pollution and climate change, yet only a limited number of isolated and geographically-restricted studies have addressed this topic, often with contrasting results. Particularities of air pollution in this region include high O3 levels due to high air temperatures and solar radiation, the stability of air masses, and dominance of dry over wet nitrogen deposition. Moreover, the unique abiotic and biotic factors (e.g., climate, vegetation type, relevance of Saharan dust inputs) modulating the response of Mediterranean ecosystems at various spatiotemporal scales make it difficult to understand, and thus predict, the consequences of human activities that cause air pollution in the Mediterranean Basin. Therefore, there is an urgent need to implement coordinated research and experimental platforms along with wider environmental monitoring networks in the region. In particular, a robust deposition monitoring network in conjunction with modelling estimates is crucial, possibly including a set of common biomonitors (ideally cryptogams, an important component of the Mediterranean vegetation), to help refine pollutant deposition maps. Additionally, increased attention must be paid to functional diversity measures in future air pollution and climate change studies to establish the necessary link between biodiversity and the provision of ecosystem services in Mediterranean ecosystems. Through a coordinated effort, the Mediterranean scientific community can fill the above-mentioned gaps and reach a greater understanding of the mechanisms underlying the combined effects of air pollution and climate change in the Mediterranean Basin. Graphical abstract: Highlights: Mediterranean Basin ecosystems are at risk due to air pollution and climate change. A more robust monitoring network in conjunction with modelling estimates is crucial. Monitoring networks should include a set of common biomonitors, ideally cryptogams. Coordinated Basin-wide biodiversity surveys along pollution gradients are needed. All this needs the coordinated effort of the Mediterranean scientific community. Abstract : A coordinated monitoring of air pollution and an assessment network of its effects are needed to improve environmental policy and management decisions in the Mediterranean Basin.